Knowledge, attitude, and practices of adolescents and peer educators in relation to the components of the National Adolescent Health Program in India: findings from a cross-sectional survey - Nayak, Gayatri; Bahl, Deepika; Bassi, Shalini; Maity, Heeya; Mason-Jones, Amanda J.; Arora, Monika; Dutta, Ambarish (Frontiers in Public Health, 2024)
Background: Adolescence is a critical period in of growth and development. Many adverse health outcomes of adulthood begin during adolescence, due to lack of knowledge and attitudes resulting from insufficient knowledge. Therefore, appropriate knowledge, attitudes and practices (KAP) regarding various aspects of health are cornerstones of holistic adolescent and lifelong health. In India, Rashtriya Kishore Swasthya Karyakram(RKSK or National Adolescent Health Strategy) engaged with adolescents through an innovative peer-education approach to improve their KAPs. Amidst scanty evidence, we aimed to assess KAP of adolescents (with special focus on the status of PEs) regarding the six themes of RKSK, disaggregated by gender, and examine how the engagement with the RKSK peer education program influenced them.Methods: A cross-sectional survey of 238 peer educators and 2885 adolescents enrolled under peer educators was conducted in two localities; Madhya Pradesh and Maharashtra states. KAPs were estimated using descriptive statistics then disaggregated by gender. Practice scores of nutrition and non-communicable disease (NCD) were modelled upon engagement with RKSK (graded as 0,1,2,3).Results: Knowledge was highest regarding substance misuse and lowest in the domains of sexual and reproductive health, violence and injury. Peer educators possessed greater knowledge in most domains RKSK engagement was associated with better nutritional practices: adjusted relative risks being 1.04(CI: 0.94-1.15), 1.12(1.04-1.21) and 1.21(1.13-1.31) respectively for engagement scores 1, 2 and 3 with reference to score 0. Relationship between RKSK engagement and non-communicable diseaserelated practices was restricted to top engagement group.The knowledge regarding sexual health and injury and violence was grossly deficient in adolescents. These components must be prioritized in the program because they are critical for health not only across the life course of individuals but also across generations. However, RKSK engagement was associated with better practices in a variety of domains which should be leveraged in future.